Analyzing spatial distribution of knowledge-intensive industries in Hungary at sub-regional level - Zsofia Vas; Izabella Szakalne Kano (European Regional Science Association (ERSA), 2010)
In recent years knowledge-intensive industries in production and services have a lead in respect of the development of knowledge-driven economy. They are now the core of growth, with an increasingly high importance especially in less developed countries, like Hungary. Spatial distribution of knowledge-intensive economic activities shows a certain inequality in Hungary, and determines the formation and existence of 'knowledge poles' described as agglomeration of knowledge-intensive industries in the country. But the fact that these industries and firms 'flock together' and have the same location, does not mean that all firms in the concentration cooperate with each other and have joint actions. It is necessary to make a differentiation between enterprises in geographical proximity (co-location) and in relational proximity. Recent study aims to identify the spatial coherence and concentration of knowledge-intensive industries in Hungary at sub-regional (LAU 1) level, using the methods and indicators of spatial econometrics. The research also tries to reveal the special characteristics of distribution of knowledge-intensive industries operating in geographical and relational proximity.
Keywords: 330